2020
DOI: 10.1177/1178633720976581
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus in the Oral Cavity: Implications for Antibiotic Prophylaxis and Surveillance

Abstract: The oral cavity harbors a multitude of commensal flora, which may constitute a repository of antibiotic resistance determinants. In the oral cavity, bacteria form biofilms, and this facilitates the acquisition of antibiotic resistance genes through horizontal gene transfer. Recent reports indicate high methicillin-resistant Staphylococcus aureus (MRSA) carriage rates in the oral cavity. Establishment of MRSA in the mouth could be enhanced by the wide usage of antibiotic prophylaxis among at-risk dental procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 180 publications
(203 reference statements)
3
24
0
1
Order By: Relevance
“…In the present study, we first revealed the prevalence and genotypes ( coa -type, ST) of MRSA and MSSA from the oral cavity of dental patients, and also the spectrum of CoNS species with their resistance phenotype and determinants. The prevalence of S. aureus and MRSA in an oral cavity reported to date varies depending on the study design having different subjects [ 33 ]. In four studies on systemically healthy dental patients, the isolation rate of S. aureus ranged from 5.9 to 36.6%, while MRSA 0–8.6% [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we first revealed the prevalence and genotypes ( coa -type, ST) of MRSA and MSSA from the oral cavity of dental patients, and also the spectrum of CoNS species with their resistance phenotype and determinants. The prevalence of S. aureus and MRSA in an oral cavity reported to date varies depending on the study design having different subjects [ 33 ]. In four studies on systemically healthy dental patients, the isolation rate of S. aureus ranged from 5.9 to 36.6%, while MRSA 0–8.6% [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-oral bacteria are transient or non-resident pathogenic bacteria that are not generally considered a common part of the oral microbiota [1]. The oral microbiota has been reported to contain more than one hundred thousand (1000) species of bacteria [2,3,4] belonging to the genera Streptococcus, Enterococcus, Staphylococcus, Actinomyces, Peptostreptococcus, Eubacterium, Treponema, Corynebacterium, Bacteroides, Lactobacillus, Fusobacterium, Leptotrichia, Campylobacter, Prophyromonas, etc., [5,6] with only a few proportions of these bacteria are associated with dental disease such as periodontitis, gingivitis, dental caries, etc., [7,8]. However, the invasion and colonization of the oral cavity by non-oral bacteria such as Staphylococci, enterococci and Gram-negative enteric rods (GNRs) depict an imbalance of oral flora in the oral cavity [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Significant proportions of humans harbour MRSA, primarily in the nasal and oral cavities but also in the perineum, axillae and hands [4,10]. It is well documented that approximately onethird of healthy people are colonized nasally with S. aureus [11] either persistently or intermittently [12]. However, the frequency of HCW colonization by MRSA and their relatedness to MRSA recovered from patient and hospital environmental sources requires further investigation [13].…”
Section: Introductionmentioning
confidence: 99%